MULTI-FREQUENCY STUDY OF SYMBIOTIC NOVAE - Chochol, D.; Pribulla, T. (Одеські астрономічні публікації, 2017)
Symbiotic novae are subclass of symbiotic stars - interacting binaries with wide orbits, whose photometric history is characterized by a single nova- like outburst lasting decades and caused by a thermonuclear runaway on the surface of a wind accreting white dwarf. Symbiotic novae have been detected in all frequencies from X-rays to radio waves. Multifrequency observations yield complementary information which appears to be crucial for an understanding of the underlying physical processes as an accretion by stellar winds, TNRs on the white dwarf, ionization of the wind from a cool giant, colliding winds, jets and bipolar outflows. The basic properties and multifrequency behaviour of the most studied objects: V1016 Cyg, V1329 Cyg, HM Sge, AG Peg, RT Ser, RR Tel and PU Vul are reviewed.